2014
DOI: 10.1109/mcom.2014.6829964
|View full text |Cite
|
Sign up to set email alerts
|

Consumer-managed federated homes

Abstract: There are emerging opportunities for distributed, composite services, based on the combination of smart homes, networked consumer devices, third-party services and social, geographical or commercial collaborations. However, current home-automation technology tends to focus on the single-home solution, rather than enabling home users can securely share and easily manage the resources and services of their home area network. This article describes a new federated home architecture that addresses these needs, rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Closer to our work, [13] also aims at building communities of users sharing home devices and services in their home networks. On the contrary to the aforementioned works, [13] does not explicitly refer to SDN, and relies on the exchange of home capabilities with peer home controllers thanks to an instant messaging and presence (IM&P) infrastructure.…”
Section: Sdn For Home Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Closer to our work, [13] also aims at building communities of users sharing home devices and services in their home networks. On the contrary to the aforementioned works, [13] does not explicitly refer to SDN, and relies on the exchange of home capabilities with peer home controllers thanks to an instant messaging and presence (IM&P) infrastructure.…”
Section: Sdn For Home Networkmentioning
confidence: 99%
“…On the contrary to the aforementioned works, [13] does not explicitly refer to SDN, and relies on the exchange of home capabilities with peer home controllers thanks to an instant messaging and presence (IM&P) infrastructure. An Home Area Network (HAN) agent performs network access control in each HAN as low level configuration orders resulting policies defined in a Federal Relationship Manager (FRM).…”
Section: Sdn For Home Networkmentioning
confidence: 99%
“…Following option 1, our solution allows the full integration of smart home and network services, while some ISPs propose only partial solutions today, either by providing evolved home gateways (e.g., Freebox 1 by Free or Livebox 2 by Orange), or very specific smart home services (e.g., Verizon Home Control 3 or Orange Smart Home 4 ). On the contrary, authors of [2] propose a solution similar to option 2.…”
Section: B Isp-managed Home Networkmentioning
confidence: 99%
“…Inspired by some previous works (e.g., [1], [2], [3]), this paper proposes a new software-based approach to delegate the control and the management of home networks to Internet Service Providers (ISPs) by virtualizing the connected devices. This paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, these structures showed that conformational features are sterically allowed in common nucleosides but actually are hardly observed. Generally, the crystal structures of cyclo arabinosides consist of five-atom fused rings, [1][2][3][4][5] but the structure of 7,2′anhydro-β-D-arabinosylorotidine (cyclo ara-O) is unusual, which in the cyclization results has a six-atom ring instead of a fiveatom ring. [6] As a result, Cyclo ara-O is one of available structures of a cyclo arabinoside with a six-atom fused ring involving the base and the 2′ position of the sugar, which corresponds to an anti conformation and is comparable with that of 6,2′-anhydro-6-ethyl-l-β-D-arabinofuranosyluracil having the similar six-atom fused ring.…”
Section: Introductionmentioning
confidence: 99%